Ki67 expression in triple negative breast cancer: Correlation of Ki67 expression with other prognostic factors in breast cancer in Indian patients - Menka Khanna; Kiranjot Kaur; Mridu Manjari; Ashish Khanna (Tropical Journal of Pathology and Microbiology, 2016)
Introduction: Triple negative breast cancer ( TNBC) cases are not sensitive to hormonal therapy and till date no specific targeted medication has been found for TNBC. The present study aims to know the expression of Ki67 in TNBC tissues and in non-TNBC tissues using immunohistochemistry and to do correlation analysis of ki 67 expression with other clinicopathological parameters.Material and Methods: The present study was conducted on 160 cases of breast cancer received as specimens from January to august 2016 in the Pathology Department, Sri Guru Ram Das institute of medical sciences, Amritsar. Histopathological typing and grading was done followed by immunohistochemistry for ER, PR, Her2neu and ki67.Results: Ki67-positive expression were identified in 86.6% TNBC cases (including 14 cases of strong Ki67 expression). By contrast, among 130 cases of non-TNBC, 98 cases were Ki67-positive, accounting for 75.3%,(only 2 cases showed strong positivity) indicating a significant difference compared with that in the TNBC group that Ki67 proliferation index was higher in the cases with size >2cm also cases with lymph node metastasis showed high Ki67 proliferation index.Conclusion: Ki-67 index is relatively higher in TNBC than in non-TNBC cases. Ki67 expression correlated with tumor size and lymph node metastasis in breast cancer in the present study. Thus the increased expression of Ki67 may predict the increased proliferation of breast cancer cells, increased invasiveness, faste r rate of growth and the high incidence of lymph node metastasis.